Hubungan Motivasi Dan Minat Belajar Dengan Hasil Belajar (Literatur Review) - Elvira Utami; Rahmadhani Fitri; Muhyiatul Fadilah (Symbiotic: Journal of Biological Education and Science, 2022)
Learning outcomes are a determinant of whether learning is good or not. The number of student learning outcomes that are not good or below the KKM. Good or poor learning outcomes are influenced by several factors, one of which is motivation and interest in learning. Each individual has a different motivation and interest in learning. Motivation and interest in learning have a relationship with learning outcomes. For this reason, a literature study was conducted. The purpose of this literature review is to see the relationship between motivation and interest in learning with learning outcomes. The data-base used in making this literature review is Google Scholar. From the 20 articles used in the literature review, it was found that there was a significant positive relationship between motivation and interest in learning and learning outcomes. learning outcomes with motivation and interest in learning have a straight relationship. It can be concluded that there is a relationship between motivation and interest in learning with learning outcomes.